(untitled) (International Journal of Built Environment and Sustainability, 2019)
In recent years gaming products have increasingly been used to enhance learning and training development in academic and commercial sectors. Games have become more pervasive; they have been adopted for use in many industries and sectors such as defence, medicine, architecture, education, and city planning and government as tools for workers development. In Malaysia, it has been reported that the construction industry holds the third highest record of occurrences of accidents at work. Therefore, safety training is inevitable to reduce the alarming rate of accidents on construction sites. However, currently, available safety training approaches are still lacking in terms of delivering hands-on training and are more theoretical- instead of being more practical-based. This is due to the nature of the construction environment itself in which safety training involving certain hazards that cannot be implemented hands-on as it may bring harm to trainers, trainees and the environment. Gaming is an approach that applies technology to provide an almost real experience with interactive field training, and also supporting the theory of learning by doing with real case scenario. The purpose of this paper is to seek and explore the differences in existing gamification genres such as simulation game, role-playing, action game, strategy game and etc. Data were collected through available literature. The findings of the study show that serious game is a suitable genre to be adopted as an approach in hazard identification training for the construction industry in Malaysia.